Perencanaan Pengendalian Produksi dan Pengawasan Kebutuhan Bahan Baku (Ppic) pada Industri Manufaktur - Firman Ardiansyah Ekoanindiyo; Widiyanto Tri Handoko; Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2008)
If material inventory too much than company need will additional interest, maintenance cost and inventory cost. Also depreciation and quality in company can not hold on. All about this will reduce company profit. If material inventory too little in company can make delay in production line so company will get lost. From survey result and distribute survey to responden that is manufactur industry in Semarang city and around all. Generally manufactur industry in Semarang city and around all PPIC to be a part from company all activity. Although all manufactur industry in Semarang city and around all have not PPIC department but they aware and concern capability dan company performance depend on planning and material controlling for reduce waste time and cost to increase productivity.